TAILoR (TelmisArtan and InsuLin Resistance in Human Immunodeficiency Virus [HIV]): An Adaptive-design, Dose-ranging Phase IIb Randomized Trial of Telmisartan for the Reduction of Insulin Resistance in HIV-positive Individuals on Combination Antiretroviral Therapy. (3rd July 2019) - Pushpakom, Sudeep; Kolamunnage-Dona, Ruwanthi; Taylor, Claire; Foster, Terry; Spowart, Cath; García-Fiñana, Marta; Kemp, Graham J; Jaki, Thomas; Khoo, Saye; Williamson, Paula; Pirmohamed, Munir; ,
Abstract: Background: Combination antiretroviral therapy results in metabolic abnormalities which increase cardiovascular disease risk. We evaluated whether telmisartan reduces insulin resistance in human immunodeficiency virus (HIV)–positive individuals on antiretrovirals. Methods: We conducted a multicenter, randomized, open-label, dose-ranging controlled trial of telmisartan. Participants with HIV infection receiving combination antiretroviral therapy were randomized equally to either no intervention (control) or 20, 40, or 80 mg telmisartan once daily. The adaptive design allowed testing of all dose(s) of telmisartan in stage I, with the promising dose(s) being taken into stage II. The primary outcome measure was reduction in homeostasis model assessment of insulin resistance (HOMA-IR) at 24 weeks. Results: A total of 377 patients were recruited. In stage I, 48, 49, 47, and 45 patients were randomized to control and 20, 40, and 80 mg telmisartan, respectively (total n = 189). At the interim analysis, 80 mg telmisartan was taken forward into stage II. At the end of stage II (n = 105, control; 106, 80-mg arm), there were no differences in HOMA-IR (estimated effect, 0.007; SE, 0.106) at 24 weeks between the telmisartan (80 mg) and nonintervention arms. Longitudinal analysis over 48 weeks showed no change in HOMA-IR, lipid or adipokine levels. There were significant ( P ≤ .05), but marginal, improvements in revised Quantitative Insulin Sensitivity Check Index (QUICKI) (0.004) and plasma hs-CRP (−0.222 mg/L) and reduction in liver fat content (1.714 mean reduction; P = .005). Conclusions: No significant effect of telmisartan was demonstrated on the primary outcome (HOMA-IR), but there were marginal improvements with some secondary outcome measures. Further studies in this population are warranted to identify novel strategies for preventing cardiovascular morbidity and mortality. Clinical Trial Registration: ISRCTN registry (51069819). Abstract : The efficacy of telmisartan in improving insulin resistance in patients with human immunodeficiency virus was investigated in an adaptive-design trial. Telmisartan had no significant effect on HOMA-IR, a measure of insulin resistance, but there were improvements with some secondary outcome measures.